Die drei populärsten «Mythen» der Accounting-Ausbildung - Marco Passardi (Swiss Journal of Business)
Certain didactic approaches to education and training in the field of accounting have become firmly established in everyday education at university level. This can lead to learning environments not being critically reflected upon and adaptation to changing circumstances not taking place often enough. In this article, the author reflects on three common «myths» that characterize this problem. The article concludes with an outlook on possible influences of digitalization in the area of future accounting education.